How Fishy was the Inland Mesolithic? New Data from Friesack, Brandenburg, Germany. Issue 5 (5th November 2018) - Meadows, John; Robson, Harry K; Groß, Daniel; Hegge, Charlotte; Lübke, Harald; Schmölcke, Ulrich; Terberger, Thomas; Gramsch, Bernhard
ABSTRACT: Recent studies have shown that faunal assemblages from Mesolithic sites in inland Northern Europe contain more fish remains than previously thought, but the archaeological and archaeozoological record does not reveal the dietary importance of aquatic species to hunter-gatherer-fishers, even at a societal level. For example, the function of bone points, as hunting weapons or fishing equipment, has long been debated. Moreover, traditional methods provide no indication of variable subsistence practices within a population. For these reasons, paleodietary studies using stable isotope analyses of human remains have become routine. We present radiocarbon ( 14 C) and stable isotope data from nine prehistoric human bones from the Early Mesolithic-Early Neolithic site of Friesack 4, and isotopic data for local terrestrial mammals (elk, red deer, roe deer, wild boar, aurochs, beaver) and freshwater fish (European eel, European perch). The reference data allow individual paleodiets to be reconstructed. Using paleodiet estimates of fish consumption, and modern values for local freshwater reservoir effects, we also calibrate human 14 C ages taking into account dietary reservoir effects. Although the number of individuals is small, it is possible to infer a decline in the dietary importance of fish from the Preboreal to the Boreal Mesolithic, and an increase in aquatic resource consumption in the Early Neolithic.